Analysis of adverse events of renal impairment related to platinum-based compounds using the Japanese Adverse Drug Event Report database. (26th April 2018) - Naganuma, Misa; Motooka, Yumi; Sasaoka, Sayaka; Hatahira, Haruna; Hasegawa, Shiori; Fukuda, Akiho; Nakao, Satoshi; Shimada, Kazuyo; Hirade, Koseki; Mori, Takayuki; Yoshimura, Tomoaki; Kato, Takeshi; et al.
Objectives: Platinum compounds cause several adverse events, such as nephrotoxicity, gastrointestinal toxicity, myelosuppression, ototoxicity, and neurotoxicity. We evaluated the incidence of renal impairment as adverse events are related to the administration of platinum compounds using the Japanese Adverse Drug Event Report database. Methods: We analyzed adverse events associated with the use of platinum compounds reported from April 2004 to November 2016. The reporting odds ratio at 95% confidence interval was used to detect the signal for each renal impairment incidence. We evaluated the time-to-onset profile of renal impairment and assessed the hazard type using Weibull shape parameter and used the applied association rule mining technique to discover undetected relationships such as possible risk factor. Results: In total, 430, 587 reports in the Japanese Adverse Drug Event Report database were analyzed. The reporting odds ratios (95% confidence interval) for renal impairment resulting from the use of cisplatin, oxaliplatin, carboplatin, and nedaplatin were 2.7 (2.5–3.0), 0.6 (0.5–0.7), 0.8 (0.7–1.0), and 1.3 (0.8–2.1), respectively. The lower limit of the reporting odds ratio (95% confidence interval) for cisplatin was >1. The median (lower–upper quartile) onset time of renal impairment following the use of platinum-based compounds was 6.0–8.0 days. The Weibull shape parameter β and 95% confidence interval upper limit of oxaliplatin were <1. In the association rule mining, the score of lift for patients who were treated with cisplatin and co-administered furosemide, loxoprofen, or pemetrexed was high. Similarly, the scores for patients with hypertension or diabetes mellitus were high. Conclusion: Our findings suggest a potential risk of renal impairment during cisplatin use in real-world setting. The present findings demonstrate that the incidence of renal impairment following cisplatin use should be closely monitored when patients are hypertensive or diabetic, or when they are co-administered furosemide, loxoprofen, or pemetrexed. In addition, healthcare professionals should closely assess a patient's background prior to treatment.